(3GdESdGe jJMOi GdedMOjf (B:s (3aUhd aj HjGf HYV BjGJ GdJMOj ddEdMGO hGdedMOjf (B/s - (3YhV, eUWai MSjfs ((3LeghQjI eUQ GdYQHjI (B:s (3JHUjQ ddfTQ hGdJhRjY ,s, 2019)
(3GdcJGH YHGQI Yf eONd def CQGO Cf jJhSY aj eSGFd GdEdMGO hGdQO Ydj GdTHgGJ jJchf ef HGHjf GdHGH GdChd(B: (3Hjf jOj GdJMOj hajgG jJMOK GdcGJH Yf MGLI GdHTQjI Edi GdOjf hCfgG YHGQI Yf aWQI QHfG NdbgG ajfG hjJWQb ajeG HYO Yf CSHGH GfMQGa GdfGS Yf GdOjf Edi GdEdMGO hefgG (B1-(3GdLgd hCbUO gfG GdLgd HfhYjg GdLgd HYdhe GdOjf hGdLgd HYdhe GdOfjG (B2-(3GdGSJeGY dTHgGJ Cgd GdEdMGO hYf NWhQI Pdc MJi dh ef HGH GdaVhd aef Gdeecf Ef Pdc jYQVg ddVdGd (B3-(3EQGOI QDjI Gddg Ke EfcGQ hLhOI HSHH YOe GSJWGYJge Pdc agPg THg ef GdTHgGJ GdeJgGaJI ceG aYdh GdjghO MjfG PGc hNUhUG Hfj ESQGFjd GdPjf de jbJfYhG hEfeG WdHhG ef ehSi Cf jQjge Gddg aYGbHge Gddg Ld hYdG HUGYbI Ke YaG Yfge MJi YHOh GdYLd adeG JGHhG JGH Gddg Ydjge acja dG jfcQ GdedMO cd eG dG jQGg ef ETYGYGJ hehLGJ UhJjI hZjQ UhJjI Hd Efg jKHJ eG dG jQGg cNQGag GdJWhQ agh de jQj cGFfG eJWhQI hdf jQj Pdc MJi jehJ (B4-(3EgeGd GdYbd hYOe GSJNOGeg ajeG Ndb dg aEf Gddg Ndb GdYbd hejR Gddg Hg GdEfSGf djchf COGJg aj GdhUhd Edi GdMb aEPG hUd Hg Edi GdMb eG Ydjg EdG Cf jJHYg (B5-(3GdbfhW hYOe JMed hLhO GdTQ aj Gdchf aEf GdEfSGf eHJdi hdG jhLO NjQ HdG TQ hEf hLhO GdTQ fGJL Yf chf GdEfSGf eNjQ hgh eG jSJNOeg GdedMOjf dg Hfaj GdEdg hgh eG jJWQb dg GdcGJH aj GdaUd GdCNjQ HJaUjd GdHGH GdKGfj (B: (3aUhd GdJMOj hajg jHjf GdcGJH Odjd GdaWQI hGdEjLGO hGdNdb hGdJUeje hGdEJbGf hUOb GdCfHjGA eSJYjfB HBjGJ GdbQBf Ke jJWQb HYO Pdc dehLgg GdCacGQ GdedMOI eKd NQGag hdGOI Gdchf ef GddG TF hGdSHHjg hjJMOK Yf HOGjg Ndb Gdchf hGdcGFfGJ GdMjg hYf JLQHg jhQj ejdQ GdaGTdg hNQGag GdJWhQ hcJGH CUd GdCfhY hGdEdMGO hGdYfUQjg HJaGUjd hGdQO Ydj cd Pdc HdZg eHSWg LOG eY hLhO HYO GdCeKdg(B.s
Keywords: (3GdEdMGO hGdedMOhfs; (3GdESdGes -- (3OaY eWGYfs